Diallyl disulfide suppresses the lipopolysaccharide-driven inflammatory response of macrophages by activating the Nrf2 pathway. (January 2022) - Zhang, Xiu-Ning; Zhao, Ning; Guo, Fang-Fang; Wang, Yi-Ran; Liu, Shi-Xuan; Zeng, Tao
Abstract: Lipopolysaccharide (LPS)-driven activation of Kupffer cells plays critical roles in the development of alcoholic liver disease (ALD). Accumulating evidence has revealed that nuclear factor erythroid 2-related factor 2 (Nrf2) can modulate the polarization of macrophages. The current study aimed to investigate the roles of diallyl disulfide (DADS) in LPS-driven inflammation in vitro and in vivo . We found that DADS significantly increased the nuclear translocation of Nrf2 and the transcription of Nrf2 targets, including HO1, NQO1, and γ-GCSc, and suppressed degradation of Nrf2 protein. Besides, DADS significantly inhibited LPS-induced activation of NF-κB and MAPK, secretion of NO and TNF-α, and production of reactive oxygen species (ROS) in LPS-exposed RAW264.7 cells. In vivo study demonstrated that DADS significantly ameliorated liver damage in mice challenged with LPS, as shown by the inhibition of increases in serum aminotransferase activities, neutrophil infiltration, and NF-κB and NLRP3 inflammasome activation. Finally, knockout of Nrf2 abrogated the suppression of DADS on macrophage polarization and on liver injury induced by LPS. These findings reveal that DADS suppresses LPS-driven inflammatory response in the liver by activating Nrf2, which suggests that the protective effects of DADS against ALD may be attributed to the modulation of Kupffer cell polarization in the liver. Graphical abstract: Image 1 Highlights: DADS activates Nrf2 signaling in RAW264.7 cells. DADS attenuates LPS-induced proinflammatory activation of RAW264.7 cells. DADS inhibits LPS-induced inflammation and liver injury in mice. Knockout of Nrf2 blunts the suppression of DADS on LPS-driven inflammatory response.